The experience of the adult with human papillomavirus infection: A scoping review - Palacios Rodríguez, Oscar Alejandro; Torres López, Teresa Margarita; Galarza Tejada, Dulce María (Población y Salud en Mesoamérica, 2020)
Objetivo: Explore what has been investigated about the experience of being diagnosed and living with Human Papillomavirus (HPV) infection in adults. Metodología: A literature review was done based on the scoping review design of Arksey and O'Malley. Resultados: The experience of the adult with HPV infection involves mainly considering four areas: psychosocial, sexual, cognitive and health care. Discusión: Although most of the findings focus on negative aspects of HPV, some show evidence of benefits or positive aspects from the diagnosis. Conclusiones: HPV carries a considerable impact from the time of its detection until the treatment, which implies affections in the different areas of the life of patients ranging from emotional issues to the adequate follow-up of the care process.